Differential Effects of Video Analysis for Special Educators Related to Intervention Characteristics, Dependent Variables, and Student Outcomes: A Meta-Analysis of Single-Case Research. Issue 4 (December 2021) - Morin, Kristi L.; Nagro, Sarah; Artis, Jonet; Haas, April; Ganz, Jennifer B.; Vannest, Kimberly J.
Video analysis is effective for changing the instructional practices of a variety of special educators in different settings and contexts; however, questions remain regarding whether (a) intervention characteristics moderate the results, (b) effects are differentiated by type of dependent variable, and (c) student outcomes improve when video analysis is used to improve educators' skills. This meta-analysis reports the overall impact that video analysis has on student outcomes as well as the differential impact on special educator outcomes by dependent variable and implementation variables (i.e., length of videos, number of intervention videos, primary evaluator, and timing of feedback). A total of 30 publications reported outcomes for special education preservice teachers, in-service teachers, and paraprofessionals; of these, 12 publications reported student outcomes. Results are positive and indicate that video analysis is effective for improving student outcomes and that it can be successfully implemented in a variety of ways.